Anticonvulsive hypersensivity syndrome due to diazepam: case report. - Safari, M.; Hosseini, F. (European Journal of Pediatric Dermatology, 2016)
Anticonvulsant hypersensitivity syndrome is an acute, life-threatening, idiosyncratic drug reaction seen with the aromatic antiepileptic drugs, phenytoin, carbamazepine, phenobarbital, and primidone. Almost always, after immediate withdrawal of the offending drug, short-acting benzodiazepines are recommended for seizure control in these cases. In the actual report a 20-month-old infant with anticonvulsive hypersensivity reaction just to diazepam was described.